2015
DOI: 10.1242/jcs.169060
|View full text |Cite
|
Sign up to set email alerts
|

The P2Y2 receptor promotes Wnt3a- and EGF-induced epithelial tubular formation by IEC6 cells by binding to integrins

Abstract: Epithelial tubular structures are essential units in various organs. Here, we used rat intestinal epithelial IEC6 cells to investigate tubulogenesis and we found that tubular formation was induced by a combination of Wnt3a and EGF signaling during threedimensional culture. Wnt3a and EGF induced the expression of the P2Y 2 receptor (P2Y 2 R, also known as P2RY2), and knockdown of P2Y 2 R suppressed tubular formation. A P2Y 2 R mutant that lacks nucleotide responsiveness rescued the phenotypes resulting from P2Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…PLA was performed according to the manufacturer's protocol (Sigma) as described previously (Ibuka et al, 2015;Osugi et al, 2019). Cells transiently expressing FLAG-VDAC2 grown on glass coverslips were fixed for 15 min at RT in PBS containing 4% PFA.…”
Section: Proximity Ligation Assaymentioning
confidence: 99%
“…PLA was performed according to the manufacturer's protocol (Sigma) as described previously (Ibuka et al, 2015;Osugi et al, 2019). Cells transiently expressing FLAG-VDAC2 grown on glass coverslips were fixed for 15 min at RT in PBS containing 4% PFA.…”
Section: Proximity Ligation Assaymentioning
confidence: 99%
“…Previous studies have demonstrated a role for the P2Y 2 R in corneal epithelial wound healing by increasing cell migration (Boucher et al, 2010), in liver regeneration by stimulating hepatocyte proliferation (Tackett et al, 2014), in cardiac regeneration by stimulating cardiac progenitor cell proliferation (Khalafalla F.G. et al, 2017) and in intestinal epithelial cell tubulogenesis (Ibuka et al, 2015). Activation of P2Y 2 Rs in the HSG cell line also induces the transactivation, homodimerization and autophosphorylation of the EGFR, a receptor tyrosine kinase known to be crucial for salivary gland branching morphogenesis and development (Miyazaki et al, 2004;Patel et al, 2006;Mizukoshi et al, 2016).…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…At the K289R mutant, the agonists ADP and UDP were more potent (four‐ and seven‐fold increased potency, respectively) than ATP and UTP (300‐ and 26‐fold decrease, respectively). Interestingly, the mutation R264L in the rat P2Y 2 R, which corresponds to Arg265 in the human receptor, had no impact on basal or ATPγS‐dependent activation, indicating that Arg264 in the rat receptor may not be involved in agonist‐induced signaling …”
Section: Mutants Of the Human P2y1‐like Receptorsmentioning
confidence: 99%
“…Interestingly, the mutation R264L in the rat P2Y 2 R, which corresponds to Arg265 in the human receptor, had no impact on basal or ATPγS-dependent activation, indicating that Arg264 in the rat receptor may not be involved in agonist-induced signaling. 42 F I G U R E 9 Schematic tree diagram of available mutagenesis data for agonist and antagonist potencies of the human P2Y 2 R…”
Section: Ligand Recognitionmentioning
confidence: 99%